Bergen’s role in the medieval North Atlantic trade (AmS-Skrifter, 2020)
North Atlantic trade in the high Middle Ages was centred on Bergen. The Bergen connection was important to the North Atlantic islanders and townsmen who specialized in trading with them, but up to the early fourteenth century did not count for much in Bergen’s total trade. This changed when larger assignments of Icelandic stockfish were sent to Bergen from the 1340s and reexported via the town’s Hanseatic settlement, the later Kontor. During the fifteenth century fish exports from the North Atlantic to Bergen declined sharply as the English increasingly fetched their fish directly from Iceland, and Hanseatic merchants from Hamburg and Lübeck followed in their wake to Iceland and the more southerly islands. Yet, in the author’s opinion, Hanseatic trade with the North Atlantic from Bergen was not reduced to the degree that has often been assumed. And it should not be overlooked that Bergen had economic relations with the North Atlantic islands outside the Hanse.